The Book of Usul At-Tarbiyah An-Nabawiyah: Pillars of Moderation in Modern Islamic Education - Fillah, Nida Uddin; Rofiq, Muhammad (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
This paper examines the book Usul At-Tarbiyah An-Nabawiyah by Abuya Sayyid Muhammad Alawi Al-Maliki as the main reference in moderate Islamic education. This book offers a comprehensive approach that pays attention to academic aspects and character building based on the values ​​of the Prophet. Through the library research method, this study analyzes the relevance of the book to the challenges of modern Islamic education, especially in the context of the digital era. The results of the study show that Usul At-Tarbiyah An-Nabawiyah provides comprehensive guidance in building a moderate Islamic education system. The concepts offered in this book, such as the balance between religious and worldly knowledge, the importance of manners before knowledge, and gradual and wise teaching methods, are still very relevant in facing today's educational challenges. By applying the principles contained in this book, it is hoped that Islamic education can produce a generation that is not only intellectually superior but also has a strong personality, upholds tolerance, and contributes to the welfare of the community.